[Ru(HNO)('py^bu^S_4_')], the first HNO complex resulting from hydride addition to a NO Complex ('py^bu^S_4_^'2-^ = 2,6-Bis(2-mercapto-3,5-di-tert-butylphenylthio)dimethylpyridine(2-)) - Sellmann, Dieter; Gottschalk-Gaudig, Thorsten; Häußinger, Daniel; Heinemann, Frank Wilhelm; Heß, Bernd Artur (Chemistry - A European Journal, 2001)
Treatment of the nitrosyl complex [Ru(NO)('pybuS4')]Br (1a) with NaBH4 in CH3OH yielded [Ru(HNO)('pybuS4')](2), which could be completely characterized. The X-ray structure determination of 2 confirmed the N coordination of the HNO ligand. Density functional theory calculations enabled us to assign the nu(NO) IR band of 2, which appears in KBr at 1358cm(-1) and in THF at 1378 cm(-1). The unprecedented hydride addition to nitrosyl complexes yielding HNO complexes fills a white spot on the map of chemical reactions, represents the as yet unknown counterpart to the well-established formyl complex formation from CO complexes and hydrides, and distinctly differs from the formation reaction of [Os(HNO)(CO)Cl2(PPh3)2], the only other HNO complex characterized structurally. The HNO complex 2 is oxidized stepwise by [Cp2Fe]PF6 in the presence of NEt3 and directly by Bronsted acids to give [Ru(NO)('pybuS4')]+ in 2e- oxidations. H+/D+ exchange indicates acidity of the HNO proton.
UnivIS-Import:2017-03-24:Pub.2001.forsch.sonder.sfb583.ruhnop